In conversation W.V. Quine. (London Philosophy International, 1994)
The program begins with a discussion of Professor Quine's early philosophical career at Harvard. This background sets the stage for a thorough discussion of Quine's naturalism, and in particular his naturalized epistemology. Questions about the famous two dogmas are raised and attention is drawn to his doctrines of existentialism and ontological relativity.
Keywords: Van Orman Quine, Willard; Van Orman Quine, Willard; Knowledge, Theory of; Naturalism